2015 Kansas Spring Annual Forage Variety Trial - J. D. Holman; A. Obour; T. Roberts; S. Maxwell; J. Kimzey (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 3 spring annual forage varieties were tested for performance at the Southwest Research-Extension Center near Garden City, KS and the Western Kansas Agriculture Research Center near Hays, KS, in 2015. Spring crops evaluated included oat and triticale.
Keywords: spring annual forage variety trial; dry matter tons per acre; hay; haylage; Kansas